Apatinib Treatment in Metastatic Gastrointestinal Stromal Tumor - Cai, Zhaolun; Chen, Xin; Zhang, Bo; Cao, Dan (Frontiers in Oncology, 2019)
Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. The clinical management of patients with metastatic GISTs is exceptionally challenging due to their poor prognosis. Apatinib is a multiple tyrosine kinase inhibitor. Here, we present the unique case with metastatic GISTs who derived clinical benefit from apatinib following the failure of imatinib and sunitinib. Case presentation: A 57-year-old man was admitted to our hospital diagnosed with metastatic and recurrent GISTs following surgical resection. Fifty-four months after the first-line imatinib treatment, he developed progressive disease, treated with cytoreductive surgery combined with imatinib. Disease progression occurred after seven months. He then received second-line sunitinib and achieved a progression-free-survival of 11 months. Apatinib mesylate was then administered. Follow-up imaging revealed a stable disease. Progression-free-survival following apatinib therapy was at least eight months. The only toxicities were hypertension and proteinuria, which were both controllable and well tolerated. Conclusions: Treatment with apatinib provides an additional option for the treatment of patients with GISTs refractory to imatinib and sunitinib.